2018
DOI: 10.1002/mma.4797
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics analysis of an HTLV‐1 infection model with mitotic division of actively infected cells and delayed CTL immune response

Abstract: In this paper, we propose an improved human T‐cell leukemia virus type 1 infection model with mitotic division of actively infected cells and delayed cytotoxic T lymphocyte immune response. By constructing suitable Lyapunov functional and using LaSalle invariance principle, we investigate the global stability of the infection‐free equilibrium of the system. Our results show that the time delay can change stability behavior of the infection equilibrium and lead to the existence of Hopf bifurcations. Finally, nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Since antigenic stimulation to generate HTLV-I specific CTLs involves a series of events that require a time delay [7]. Therefore, it is necessary to consider the effect of time delay in the model, and the form of CTL immune function f (y, z) = cy(t − τ ) has been used in [14]. Motivated by the works of Li and Shu [16], Lim and Maini [17], in this paper, we consider the following HTLV-I infection model with actively infected CD4 + T cells mitosis and delayed CTL immune response:…”
Section: Introductionmentioning
confidence: 99%
“…Since antigenic stimulation to generate HTLV-I specific CTLs involves a series of events that require a time delay [7]. Therefore, it is necessary to consider the effect of time delay in the model, and the form of CTL immune function f (y, z) = cy(t − τ ) has been used in [14]. Motivated by the works of Li and Shu [16], Lim and Maini [17], in this paper, we consider the following HTLV-I infection model with actively infected CD4 + T cells mitosis and delayed CTL immune response:…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] and [ 31 34 ]). HTLV-I dynamics models with the mitotic division of Tax-expressing HTLV-infected cells and CTL immune response have been developed in [ 15 , 35 – 37 ]. Li and Zhou [ 36 ] have assumed that Tax-expressing HTLV-infected cells proliferate at rate , with staying in the Tax-expressing HTLV-infected cells compartment, while being silent and, therefore, escaping from the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…As studies of complexities in physics, tumor-associated responses can be better approached by establishing mathematical models with some appropriate simplified assumptions than via experimental procedures alone. [3][4][5][6] Over the last two decades, tumor immunology has attracted remarkable attention and various mathematical models have been developed to understand the interaction between cancer and immune cells. A review of early works concerning tumor-immune interactions can be found in Adam and Bellomo 7 and Eftimie et al 8 Given the complexity of this process, many models include four or more variables or equations.…”
Section: Introductionmentioning
confidence: 99%